2004
DOI: 10.1081/clt-120039542
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Episodes of Endosulfan Poisoning

Abstract: Contamination of wheat grains or flour with endosulfan and its consumption over a period of time was the most likely cause of repeated episodes of convulsions, but the exact reason for this contamination could not be determined. This report highlights the unsafe disposal of pesticide containers by illiterate farm workers, superstitions leading to delay in treatment, and susceptibility of children to endosulfan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 7 publications
1
20
0
2
Order By: Relevance
“…Our data demonstrated that frequent application of pesticides induced toxicity similar to that of repeated sublethal doses of pesticides, which may cause a tremendous alteration in the levels of liver enzymes [42]. It can be concluded that long-term occupational exposure to pesticides may result in cumulative leakage of enzymes as in the work of Dewan et al [44] which may resulting in severe damage of hepatic cells, hepatocytes and/or other body organs. Consequently accumulation of the enzymes in the blood serum may occur.…”
Section: Demographic and Occupational Parametersmentioning
confidence: 53%
“…Our data demonstrated that frequent application of pesticides induced toxicity similar to that of repeated sublethal doses of pesticides, which may cause a tremendous alteration in the levels of liver enzymes [42]. It can be concluded that long-term occupational exposure to pesticides may result in cumulative leakage of enzymes as in the work of Dewan et al [44] which may resulting in severe damage of hepatic cells, hepatocytes and/or other body organs. Consequently accumulation of the enzymes in the blood serum may occur.…”
Section: Demographic and Occupational Parametersmentioning
confidence: 53%
“…Furthermore, endosulfan, which is banned in many countries due to its persistence and bio-accumulative properties, was used by more than 20% of the study participants. Endosulfan together with other modern pesticides that are frequently applied in the study area are likely to induce neurotoxic as well as other toxic effects in chronically exposed humans as previously described [37][38][39]. It is well documented that the nervous system represents a key target for both acute and chronic effects of pesticides [9,20].…”
Section: Discussionmentioning
confidence: 99%
“…Bu durumun 10 gün boyunca sürdü¤ü ve endosülfan›n 23 saat boyunca serum konsantrasyonunun 0,12 mg düzeyin-de izlendi¤i belirtilmifltir (10). Dewan ve arkadafllar› Hindistan'da bir tar›m bölgesinde endosülfana kronik olarak maruz kalan birkaç ailede tekrarlayan konvülzi-yon nöbetleri oldu¤unu gözlemlemifllerdir (11). Baflka bir çal›flmada Darren ve arkadafllar›, Srilanka'da endosül-fana maruz kalan bir kiflide status epileptikus görüldü¤ü-nü belirtmifller ve bunun sebebini endosülfan'›n major inhibitör nörotransmitterler olan GABA (gama amino bütirik asid) ve Glycin'i inhibe etmesine ba¤lam›fllard›r (12).…”
Section: Tartifimaunclassified
“…Ayr›ca yap›lan birçok çal›flmada endosülfan zehirlenmesinin temel olarak k›rsal bölgelerde görüldü¤ü, ço¤un-lukla kaza sonucu daha nadir olarak da intihar amaçl› toksikasyonlara rastland›¤› belirtilmektedir (10)(11)(12)(13)(14)(15). Olgular›m›zda endosülfan›n içilen sütlerin içinde tespit edilmesi kaza ya da intihar olas›l›¤›ndan uzaklaflt›rmak-tad›r.…”
Section: Tartifimaunclassified